Comparing the effects of whole-body vibration to standard exercise in ambulatory people with Multiple Sclerosis: a randomised controlled feasibility study. (July 2016) - Uszynski, Marcin Kacper; Purtill, Helen; Donnelly, Alan; Coote, Susan
Objectives: This study aimed firstly to investigate the feasibility of the study protocol and outcome measures, secondly to obtain data in order to inform the power calculations for a larger randomised controlled trial, and finally to investigate if whole-body vibration (WBV) is more effective than the same duration and intensity of standard exercises (EXE) in people with Multiple Sclerosis (PwMS). Design: Randomised controlled feasibility study. Setting: Outpatient MS centre. Subjects: Twenty seven PwMS (age mean (SD) 48.1 (11.2)) with minimal gait impairments. Interventions: Twelve weeks of WBV or standard EXE, three times weekly. Main measures: Participants were measured with isokinetic muscle strength, vibration threshold, Timed Up and Go test (TUG), Mini-BESTest (MBT), 6 Minute Walk test (6MWT), Multiple Sclerosis Impact Scale 29 (MSIS 29), Modified Fatigue Impact Scale (MFIS) and Verbal Analogue scale for sensation (VAS) pre and post 12 week intervention. Results: WBV intervention was found feasible with low drop-out rate (11.1%) and high compliance (90%). Data suggest that a sample of 52 in each group would be sufficient to detect a moderate effect size, with 80% power and 5% significance for 6 minute walk test. Large effect sizes in favour of standard exercise were found for vibration threshold at 5th metatarsophalangeal joint and heel ( P =0.014, r= 0.5 and P =0.005, r=0.56 respectively). No between group differences were found for muscle strength, balance or gait ( P >0.05). Conclusions: Data suggest that the protocol is feasible, there were no adverse effects. A trial including 120 people would be needed to detect an effect on walking endurance.